“ZOMBIES AND COWYBOYS: HOW TO WIN THE APOCALYPSE” - Anderson, Mark Cronlund (European Scientific Journal, ESJ, 2014)
―Zombies and Cowyboys: How to Win the Apocalypse ‖ Suddenly zombies are everywhere. From graphic novels to Hollywood, from academic treatises asking us to consider the real-world implications of a zombie invasion to prime time television series. The undead haunt us as never before. The most common scholarly responses to the irruption of zombie popularity have noted the more than coincidental association with 9/11. Put simply, American popular culture has reacted to 9/11, for a variety of reasons identified by scholars, by churning out tales of a zombie apocalypse much as it had, though to a lesser extent, when the zombie film first emerged as a response and reaction to the cold war in the 1950s. Taken literally, the zombie invasion of course threatens American (and the world‘s) very survival. It becomes a game changer. It calls for entirely new rules, the emerging new roles of zombie interpretation suggest. Or does it? The phenomenon of the apparently unprecedented zombie onslaught in the wake of and as a response to 9/11, likely reflects something far more prosaic—in other words, a continuance more than a rupture. For example, AMC‘s hugely popular dystopic zombie series, TheWalking Dead, set in real time in the American south, relies on the deepest of American narrative tropes—the frontier cowboy, to carry its story of resistance and rebirth. In this way, while zombies may conjure up a fright symbolically akin to that rendered by 9/11 (or the martial response to 9/11), or may have been feasting on American trauma borne of 9/11 (or to the trauma of the ensuing wars), not to worry, the cowboy—that is, in the serie, Rick—can still best solve America‘s (and thereby the world‘s) problems. As such, The Walking Dead is really fairly banal, a classic example of adapting an age-old genre to fit contemporary events. This cuts two ways because, yes, it fits the classic zombie mold. But it runs deeper, too, because the frontier tale in fact is America‘s birth story, as old as the settler nation itself. In other words, The Walking Dead serves the highly useful purpose of symbolic rebirth, American-style. Cowboy Rick plays the role of proto American messiah. My paper explores how and why zombies ultimately stand no chance against Rick, The Walking Dead‘s cowboy protagonist, Carl, Rick‘s son and cowboy-in-the-making.